2022
DOI: 10.3390/antibiotics11060782
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Genes, Plasmids, Multilocus Sequence Typing (MLST), and Phenotypic Resistance of Non-Typhoidal Salmonella (NTS) Isolated from Slaughtered Chickens in Burkina Faso

Abstract: The emergence of antimicrobial-resistant bacteria in developing countries increases risks to the health of both such countries’ residents and the global community due to international travel. It is consequently necessary to investigate antimicrobial-resistant pathogens in countries such as Burkina Faso, where surveillance data are not available. To study the epidemiology of antibiotic resistance in Salmonella, 102 Salmonella strains isolated from slaughtered chickens were subjected to whole-genome sequencing (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…From the MLST analysis, the 114 strains were categorized into 34 STs, with ST40, ST11, and ST26 emerging as the most frequent STs, accounting for 11.4% (13/114), 11.4% (13/114), and 8.8% (10/114) of the isolates, respectively (Table 1). It has been observed that S. Typhimurium comprises ST19 (7), ST34 (9), and ST36 (1), while S. Derby encompasses ST40 (13) and ST71 (1); other serotypes were identified unique STs. A The correlation of STs among strains from different sources is shown in Fig 5B . Five sequence types, namely ST13, ST26, ST34, ST40, and ST358 were identified in samples from in food, asymptomatic carriers, and clinical cases samples.…”
Section: Mlst Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…From the MLST analysis, the 114 strains were categorized into 34 STs, with ST40, ST11, and ST26 emerging as the most frequent STs, accounting for 11.4% (13/114), 11.4% (13/114), and 8.8% (10/114) of the isolates, respectively (Table 1). It has been observed that S. Typhimurium comprises ST19 (7), ST34 (9), and ST36 (1), while S. Derby encompasses ST40 (13) and ST71 (1); other serotypes were identified unique STs. A The correlation of STs among strains from different sources is shown in Fig 5B . Five sequence types, namely ST13, ST26, ST34, ST40, and ST358 were identified in samples from in food, asymptomatic carriers, and clinical cases samples.…”
Section: Mlst Profilesmentioning
confidence: 99%
“…Several reports have highlighted the circulation of Salmonella spp. among animals, humans, and the environment [ 9 ]. Typing and tracing Salmonella subsequent to isolation and identification are crucial for epidemiological investigations, ensuring food safety, safeguarding public health, and optimizing livestock production [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, a multi-country outbreak of Salmonella Saintpaul was linked to raw tomatoes in the United States, affecting several states and causing 1500 case subjects, 21% were hospitalized, and 2 died [9]. Unfortunately, in Burkina Faso, many cases of outbreak caused by foodborne pathogens such as Salmonella or E. coli are still unreported [10].…”
Section: Introductionmentioning
confidence: 99%